ANALISIS DISKRIPTIP KUALITATIP HASIL UN SMP KABUPATEN KLATEN TAHUN PELAJARAN 2010 / 2011 - ., Gunarto (MAGISTRA, 2012)
Gunarto, teacher, The Analysis Descriptive Qualitative of The National  Final Examination at the JuniorHigh School, The Years Course 2010/2011.The Analysis Descriptive Qualitative of the National Final Examination (UN) at the Junior High School,Years Course 2010/2011, aiming at the Documents Result on the subjects; Indonesian, English, Mathematics,and Physics (IPA), that had been determinated by the Centre of National Estimation by the Minister of Educationand spread using the information system of the National Final Examination in 2011. The Data Analysis thathad been used by the writer using the qualitative and quantitative analysis.The aims of this writing are: 1.  This writing gives the  decipherments result of the National FinalExamination, for the Junior High School, so that it makes easier to read and knew by the public society whoneed it; 2. Knowing the completing criteria of the students for each lessons which is national tested;           3.Knowing the rank position of Klaten Regency in Ex Surakarta Residency at Jawa Tengah.The Analysis Results are: 1. Showing that at the grade of Junior High School in Klaten Regency, at theYears Course 2010/2011, is  85,953% (13.229) passed from 15.391. The  calculation based on  ReachingCompetence Standard (SKL) which has been made by The Ministry of Education that is, the sum of four markingfor the lessons which is tested must have at least 22 (twenty two) and there is no one or more lessons that haveat least minus from 4 (four); 2. The position of Klaten Regency based on the National Final Examinationsresult at the Years Course 2010/2011 is on the 3th (third) position at Ex Surakarta Residency, and on the 13th(thirteenth) position at the province; 3. The percentage of having a misscarriage, reached 85,953%, it meansthat the learning process in Klaten Regency has been reached.The result conclusion of the National Final Examination at the Junior High School in Klaten Regency in2011 reached the good result, that is why it must be maintained and must have more increasing, so that thefailure marking in the next year is lesser than it is now.Keywords: UN (National Final Examination), SKL (Reaching Competence Standard)